To robber flies fauna (Diptera: Asilidae) of Mordovia, Russia - DMITRY M ASTAKHOV; ALEXANDER B RUCHIN; OLGA D ROMADINA; IVAN M PRISTREM (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. On the basis of long-term data (2007-2018), the fauna of robber flies (Asilidae) of the Republic of Mordovia was studied. Taking into account our own and literary data, 35 species of robber flies from 18 genera were noted. Of them, 19 species were noticed in the Republic of Mordovia for the first time. We presented the photos of morphological traits of Choerades fuliginosa (Panzer, [1798]), Choerades gilva (Linnaeus, 1758), Choerades ignea (Meigen, 1820), Laphria gibbosa (Linnaeus, 1758), Andrenosoma albibarbe (Meigen, 1820), Andrenosoma atra (Linnaeus, 1758), Didysmachus picipes (Meigen, 1820), Dysmachus stylifer (Loew, 1854), Pamponerus germanicus (Linnaeus, 1758), Philonicus albiceps (Meigen, 1820), Machimus gonatistes (Zeller,1840), Neoitamus cothurnatus (Meigen,1820), Neoitamus cyanurus (Loew, 1849), Dioctria atricapilla Meigen, 1804, Leptogaster cylindrica (De Geer, 1776).